The myth of septic complications of acute pneumonia - Igor Klepikov (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2021)
A new era in the treatment of Acute Pneumonia (AP) began with the introduction of antibiotics into medical practice. The first successes of the use of new drugs were accompanied by a gradual simplification of views on the nature of AP with an emphasis on the characteristics of the pathogen and its suppression. A huge layer of scientific materials that allow us to understand the features of the development and course of inflammatory processes in the lungs, remained unclaimed. The focus on the etiology of the disease has led to a distorted view of its mechanisms and an exaggerated diagnosis of septic complications that do not have a reasoned confirmation. The current pandemic with a large number of COVID-19 pneumonias has radically changed the etiology of AP and deprived practical medicine of conventional treatment regimens. The unpreparedness of modern medicine for such a challenge and the preservation of the previous ideology of the disease are the reason for a radical revision of the AP doctrine.